Fistulotomy versus Fistulectomy for Fistula-in-Ano: A Randomized Prospective Study - Hiremath, Srikantaiah Chandra Sekhariah; Patil, Rakesh (The Surgery Journal, 2022)
Background Fistula-in-ano is common surgical ailment yet challenging to treat. Current management remains majorly dependent on two conventional surgical options (fistulotomy and fistulectomy), surgeon's preference, and their experience.Methods This prospective, randomized study was conducted to compare fistulotomy with fistulectomy in the management of patients with simple fistula-in-ano. Fifty patients were recruited and randomized into two groups each containing 25 patients: group I was managed by fistulotomy and group II was managed by fistulectomy. The outcomes of the study include operating time, postsurgery hospital stay, wound healing time, postoperative pain, and postoperative complications.Results Of the 50 patients, 11 (22%) were female and 39 (78%) were male with a mean age of 40.62 ± 12.86 years. The operating time in patients in the fistulotomy group was 21.96 ± 1.90 minutes and in the fistulectomy group was 31.32 ± 2.99 minutes (p ≤ 0.001). The mean postsurgical hospital stay in the fistulotomy group was 1.32 ± 0.47 days and in the fistulectomy group was 2.32 ± 0.69 days (p ≤ 0.001), respectively. Mean Visual Analog Scale score was higher in fistulectomy when compared with the fistulotomy at 6 hours and at discharge (p ≤ 0.05). Postoperative complications were also found to be less in fistulotomy patients compared with patients who underwent fistulectomy.Conclusion In comparison to a fistulectomy, fistulotomy has a slight edge in terms of operating time, postsurgery hospital stay, wound healing time, postoperative pain, and postoperative complications. Fistulotomy yielded better results than fistulectomy and we recommend fistulotomy procedure as a treatment of choice in patients with simple low lying fistula-in-ano.
Keywords: fistulotomy; fistulectomy; fistula-in-ano; prospective study